Insulation workers in Belfast. A further study of mortality due to asbestos exposure (1940-75). Issue 3 (August 1977) - Elmes, P C; Simpson, M J
Abstract : A follow-up study of 162 men already working as insulators (laggers) in 1940 has been extended from 1965 to 1975. By the end of 1975 there were 40 survivors when 108 had been expected. Until 1965 there had been an overall excess of deaths; these were due to asbestosis with or without tuberculosis and to alimentary cancer, as well as to bronchial carcinoma and mesothelioma. From 1965 onwards the overall death rate among survivors is not so excessive but there is still a marked excess of deaths from bronchial cancer and mesothelioma. The continued risk of death attributable to malignancy after asbestosis had ceased to contribute directly, does not appear to be caused by any changes which occurred before 1940 in the conditions at work.